Sulforaphane and Epigallocatechin Gallate Restore Estrogen Receptor Expression by Modulating Epigenetic Events in the Breast Cancer Cell Line MDA-MB-231: A Systematic Review and Meta-Analysis - Gianfredi, Vincenza; Vannini, Samuele; Moretti, Massimo; Villarini, Milena; Bragazzi, Nicola Luigi; Izzotti, Alberto; Nucci, Daniele (Journal of nutrigenetics and nutrigenomics, 2017)
Background/Aims: Epigenetics refers to modifications in gene activity and expression without alteration at the DNA sequence. Environment and diet could influence gene expression. Diet modifications may be meaningful in preventing and treating chronic diseases, cancer included. Dietary bioactive compounds, such as polyphenols (e.g., curcumin, resveratrol, or epigallocatechin gallate [EGCG]) or isothiocyanate (e.g., sulforaphane [SFN]), can regulate histone acetylation. The aim of this systematic review and meta-analysis was to evaluate the effect of SFN and EGCG on breast cancer (BC) cells cultured in vitro. Methods: Due to the enormous variability observed in study protocols and the innumerable genes involved, only studies analyzing the number of apoptotic cells in the MDA-MB-231 cell line were evaluated. The effect size (ES) was computed as the ratio of means. Results: We identified 7 studies, 4 regarding the effect of 10 µ M SFN on MDA-MB-231 cells (ES = 4.59, 95% confidence interval 4.05-5.20) and 3 focusing on the impact of 20 µ M EGCG (ES = 2.84, 95% confidence interval 2.60-3.10). Conclusion: The findings suggest beneficial effects of dietary bioactive compounds such as SFN and EGCG and their effect on BC cells by restoring estrogen receptor gene expression, modulating epigenetic changes and events, and interfering with tumor growth rate. Publication bias limits the generalizability of the conclusions. High-quality studies are needed.